Just in time: a new modality for community via networks - Allen, Matthew (AoIR Selected Papers of Internet Research, 2013)
My paper reviews the significance of the term community in attempts to understand the social and human dimensions of computer-mediated communication in light of the current dominance of self-interested social networking as the primary form of internet use. Exploring the two ways in which place has been used to articulate the relationship of individuals and collectives, the paper proposes the necessity of moving instead to explore time and rhythm in a world where networks are ‘everywhere and nowhere’, thus rendering space a consequence of our temporal synchronicities, rather than a precursor